Formação de professores da Educação de Jovens e Adultos na Rede de Aprendizagem e Desenvolvimento da Docência da UFSCar - Abreu, Cremilda Peres Cangussu de (Universidade Federal de São Carlos, 2026)
This research, centered on teacher education, aimed to analyze elements of Teacher Learning and Professional Development experienced by undergraduate students in Pedagogy and by novice and experienced teachers from Youth and Adult Education (EJA) during their participation in an extension activity carried out within the Teaching Learning and Development Network (ReAD), in the Moodle environment of UFSCar. The investigation adopted a qualitative approach with collaborative aspects. For data collection, questionnaires, interviews, logbooks, and written narratives produced in the context of an online extension activity offered by the Federal University of São Carlos (UFSCar) were used, totaling 120 hours between January and July 2024. The educational activity had a dual purpose, both research and teacher education, and involved undergraduate Pedagogy students from UFSCar and from the Federal University of the South and Southeast of Pará (Unifesspa), in addition to Youth and Adult Education (EJA) teachers from municipal and state public schools in the south and southeast of the state. The data were processed and categorized based on Bardin’s Content Analysis technique. The results were organized into categories and subcategories which allowed analyzing: a) the participants’ perspectives on teaching; b) the manifestations of the demands, challenges, and possibilities of EJA in the context of ReAD/UFSCar; c) reflections on the contributions of the experiences to practical knowledge in EJA within the scope of ReAD/UFSCar; and d) the potentialities and limitations of the online extension activities from the perspective of Pedagogy undergraduate students and EJA teachers, based on the supporting literature and the objectives of the study. The analyses show that the online extension activities in ReAD contributed significantly to the appreciation of intergenerational dialogue among students and novice and experienced EJA teachers. This dialogue, built around theoretical and methodological approaches and the sharing of individual and collective experiences, fostered new learning experiences within the teaching context. As an educational and collaborative space, ReAD showed strong potential for the education of undergraduate students and practicing teachers by promoting and strengthening teacher agency. Furthermore, participants highlighted that the online educational process stimulated reflection on teaching and the investigation of pedagogical practices, broadening theoretical and practical knowledge and promoting new learning experiences, as well as personal and professional development for teachers. The research also indicated that demands in the field of EJA, such as the adaptation of curriculum proposals, the inclusion of EJA in academic debates, and the revision of pedagogical practices, are pathways for new investigations, for strengthening academic production, and for expanding content in future teacher education programs, in accordance with the specificities of Youth and Adult Education. We concluded that, despite the difficulties related to the scarcity of technological resources among participating teachers and limited access to reliable internet, the participants acknowledged the relevance and broad accessibility of the online extension activities, which expanded opportunities for teacher education in regions geographically far from the country’s major educational hubs.
Teacher training for Youth and Adult Education within the UFSCar Teacher Learning and Development Network
Keywords: Formação de professores; Aprendizagem e Desenvolvimento Profissional da Docência; Educação de Jovens e Adultos e idosos; Juvenilização na EJA; Diálogo intergeracional; Teacher education; Teacher Learning and Professional Development; Youth, Adult, and Older Adult Education; Youthification of EJA; Intergenerational dialogue; CIENCIAS HUMANAS; 4. Educação de Qualidade